2016
DOI: 10.31219/osf.io/6yugk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strategy selection as rational metareasoning

Abstract: Many contemporary accounts of human reasoning assume that the mind is equipped with multiple heuristics that could be deployed to perform a given task. This raises the question of how the mind determines when to use which heuristic. To answer this question, we developed a rational model of strategy selection, based on the theory of rational metareasoning developed in the artificial intelligence literature. According to our model people learn to efficiently choose the strategy with the best cost-benefit tradeof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Furthermore, the LVOC model's sophistication may be necessary to explain more complex phenomena such as how people learn to orchestrate their thoughts to solve complex problems and acquire sophisticated cognitive strategies. Recent work has indeed shown that the learning mechanism instantiated by the LVOC model can also capture aspects of how people learn how to plan [70] and to flexibly and adaptively choose between alternative cognitive strategies [53]. Testing whether people learn to select sequences of control signals in the way predicted by our model is an interesting direction for future research.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Furthermore, the LVOC model's sophistication may be necessary to explain more complex phenomena such as how people learn to orchestrate their thoughts to solve complex problems and acquire sophisticated cognitive strategies. Recent work has indeed shown that the learning mechanism instantiated by the LVOC model can also capture aspects of how people learn how to plan [70] and to flexibly and adaptively choose between alternative cognitive strategies [53]. Testing whether people learn to select sequences of control signals in the way predicted by our model is an interesting direction for future research.…”
Section: Discussionmentioning
confidence: 95%
“…In many real-world scenarios and some experiments, the opportunity cost is time-varying. This can be incorporated into our model by adding a learning mechanism that estimates ω from experience [52,53]. Following [46], we model the intrinsic cost of control as the implementation cost…”
Section: Krebs Et Al (2010) Expmentioning
confidence: 99%
See 2 more Smart Citations
“…Choosing a cognitive system can be construed as metareasoning: deciding how to deploy cognitive resources in an efficient manner, considering both the expected utility and expected costs rather than using the most accurate strategy regardless of resource usage (Russell and Wefald 1991). This framework has been shown to explain general human strategy selection (Lieder and Griffiths 2017;Payne et al 1988) and has been used to describe how people allocate cognitive resources within a strategy for physical prediction (Hamrick et al 2015).…”
Section: Metareasoning Over Cognitive Systemsmentioning
confidence: 99%